Alternative uses of didactics scripts and anatomy models in the teaching-learning in practical human anatomy - Gleidially Nayara Bezerra Moraes; Paulo Adriano Schwingel; Edivaldo Xavier Silva Júnior (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
The teaching and learning process is complex and difficult presented with respect to the human anatomy. Thus, the improvement of teaching resources applied to the teaching of this discipline, shows up as a satisfactory trend and encourages student participation as an active subject in the search for new informations, giving essential support teaching-learning process. The aim of the study was to verify the existence and utilization of teaching scripts and anatomical models in practicals classes of Human Anatomy. The study was a descriptive systematic review, developed with scientific production indexed in electronic databases LILACS, MEDLINE, GOOGLE ACADEMICO and SciELO; as well as Brazilian proceedings. Among the 17 articles found, 9 showed the use of anatomical models, 7 showed other methods used, and only 1 on the use of didactic manual on classroom practice of this discipline. From the study, it can be observed that the use of teaching scripts for teaching in practical classes of Human Anatomy is an innovative method and the use of anatomical models alternative has shown positive results in the teaching-learning process. However, these methods, ever can replace the use of the corpse in the teaching of this discipline.